Two new species of mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) from Japan - Tanaka, Hirotaka; Sasaki, Daisuke; Choi, Jinyeong; Husnik, Filip; Kamitani, Satoshi (Zootaxa, 2022)
Two new mealybug species (Hemiptera: Coccomorpha: Pseudococcidae), namely, Dysmicoccus kunaw Tanaka sp. nov. and Phenacoccus miruku Tanaka & Choi sp. nov., collected in Japan, are described based on the morphological characteristics of the adult females. Dysmicoccus kunaw resembles D. trispinosus (Hall 1923) and D. furcillosus Williams 2004, but differs from them in having two conical cerarian setae in each anal lobe cerarius, a considerable number of dorsal multilocular pores on the abdominal segments, and two types of oral collar tubular ducts on the venter. Phenacoccus miruku is similar to P. sisymbriifolium Granara de Willink 2007 and P. similis Granara de Willink 1983, but differs by lacking quinqelocular pores anterior to the mouthparts and translucent pores on the hind tibiae, and in the shape of the circulus. A molecular phylogenetic analysis was used to investigate the phylogenetic placements of the two new species. Keys to the species of Dysmicoccus Ferris and Phenacoccus Cockerell found in Japan are provided.